Total Phenol, Flavonoid Content, and Antioxidant Activity of the Ethanol Fraction of Arcangelisia Flava Stem - Fatmawati, Fatmawati; Oktharina, Eka Handayani; Mulawarman, Hisham; Sinulingga, Sadakata; Safyudin, Safyudin (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Oxidative stress caused by an imbalance between reactive oxygen species (ROS) production and antioxidant defenses leads to various diseases. Arcangelisia flava, a medicinal plant, contains antioxidant-active phenols and flavonoids. This study evaluates the total phenol and flavonoid content and the antioxidant activity of the ethanol fraction of A. flava stem. Methods. An experimental study was conducted using 750 grams of A. flava stem. The sample underwent fractionation and was analyzed using Folin-Ciocalteu and AlCl3 methods to determine total phenol and flavonoid content. Antioxidant activity was assessed using the DPPH method. Data were analyzed using regression equations and IC50 values. Results. The ethanol fraction contained 57.81 ± 3.28 mg GAE/g of total phenol and 114.6 ± 1.02 mg QE/g of total flavonoid. The IC50 value for the ethanol fraction was 72.88 ppm, indicating strong antioxidant activity, albeit less potent than ascorbic acid (IC50 7.37 ppm). Conclusion. The ethanol fraction of A. flava stem is a potential natural antioxidant source.